The Seasonal Distribution of Molluscan (Bivalvia and Gastropoda) Biodiversity in Riva Stream (Istanbul) - Serap Koşal Şahin; Nilay Dökümcü (Aquatic Sciences and Engineering, 2022)
Mollusk samples were collected between March 2018 and January 2019 through seasonal sampling at five stations [Riva (ST1), Kuzdere (ST2), Kanlıdere (ST3), Atdosun (ST4), Değirmendere (ST5)] of Riva Stream (Istanbul). In the study, 7,073 individuals, 7 taxa [1 species belonging to Prosobranchia (Bithyniasp.),3speciesbelongingtoPulmonata(Planorbisplanorbis(Linnaeus,1758),Physella acuta (Draparnaud, 1805) and Gyraulus albus (O. F. Müller, 1774) and 3 species belonging to Bival-via[Pisidiumcasertanum(Poli1791),Pisidiumamnicum(Muller,1774)andSphaeriumcorneum(Linnaeus, 1758)] were determined. Considering the dominance (%) of taxa, Bithynia sp. was deter-mined as the most dominant species among all stations (5,479 individuals (77.46%)). During sam-pling, various environmental variables [depth (cm), width (cm), flow rate (m/s), water temperature (oC), dissolved oxygen (%), pH, conductivity (μS/cm), salinity (ppm), NH4-N (mg/L), NO3-N (mg/L), NO2-N (mg/L), PO4-P (mg/L), TP (mg/L) and TSS (g/L)] were measured. The relationship between environmental variables and taxa was determined using Canonical Correspondence Analysis (CCA) using the Past Statistics Program, version 4.02. The clustering relationship between the five sam-pling stations and the unweighted pair group method (UPGMA) with arithmetic mean was shown.